The Relationship between Religiosity and Empty Nest Syndrome in the Elderly - Dyah Ayu Puspitasari; Lely Ika Maryanti (Indonesian Journal of Islamic Studies, 2021)
Empty nest syndrome is a description of feelings of emptiness or emptiness that can be indicated by empty feelings such as loss, sadness, depression that elderly people feel when their children leave the house where they grew up. The factor that is thought to contribute to the height or the size of the empty nest syndrome is religiosity. Religiosity is a state within the individual where the situation can influence the daily actions and behavior of Muslims to conform to Islamic teachings and practices. The purpose of this study was to determine the relationship between religiosity and empty nest syndrome in the elderly in Larangan Village, Sidoarjo. The subjects in this study amounted to 157 people with Non-Probability sampling technique with quota sampling method. Subject criteria are elderly who are over 60 years old, are in the prohibition market area, Sidoarjo, and have empty nest symptoms such as loneliness, emptiness in married life. Methods of data collection using the scale of religiosity and empty nest syndrome scale. Data analysis used product moment correlation data analysis with the results obtained (r = -0.631; = 0.000). This shows that there is a negative relationship between religiosity and empty nest syndrome, which means that the higher the religiosity, the lower the empty nest syndrome, and the lower the religiosity, the higher the empty nest syndrome.